Effects of sensorineural hearing loss on temporal coding of harmonic and inharmonic tone complexes in the auditory nerve - Kale, Sushrut (2013)
Listeners with sensorineural hearing loss (SNHL) often show poorer thresholds for fundamental-frequency (F0) discrimination, and poorer discrimination between harmonic and frequency-shifted (inharmonic) complex tones, than normal-hearing (NH) listeners—especially when these tones contain resolved or partially resolved components. It has been suggested that these perceptual deficits reflect reduced access to temporal-fine-structure (TFS) information, and could be due to degraded phase-locking in the auditory nerve (AN) with SNHL. In the present study, TFS and temporal-envelope (ENV) cues in single AN-fiber responses to bandpass-filtered harmonic and inharmonic complex tones were measured in chinchillas with either normal hearing or noise-induced SNHL. The stimuli were comparable to those used in recent psychophysical studies of F0 and harmonic/inharmonic discrimination. As in those studies, the rank of the center component was manipulated to produce different resolvability conditions, different phase relationships (cosine and random phase) were tested, and background noise was present. Neural TFS and ENV cues were quantified using cross-correlation coefficients computed using shuffled cross-correlograms between neural responses to REF (harmonic) and TEST (F0- or frequency-shifted) stimuli. In animals with SNHL, AN-fiber tuning curves showed elevated thresholds, broadened tuning, best-frequency shifts, and downward shifts in the dominant TFS response component; however, no significant degradation in the ability of AN fibers to encode TFS or ENV cues was found. Consistent with optimal-observer analyses, the results indicate that TFS and ENV cues depended only on the relevant frequency shift in Hz and thus were not degraded because phase-locking remained intact. These results suggest that perceptual “TFS-processing” deficits do not simply reflect degraded phase-locking at the level of the AN. To the extent that performance in F0 and harmonic/inharmonic discrimination tasks depend on TFS cues, it is likely through a more complicated (sub-optimal) decoding mechanism, which may involve “spatiotemporal” (place-time) neural representations.